The Impact of Elements of the Organizational Climate in the Management of University Performance, A Survey Study of the Views of a Sample of Faculty Members at Al-Muthanna University - joudeh jasim, majid; jasim hamoud, salam (Iraqi Journal for Administrative Sciences, 2025)
This study aimed to Explore the relationship between the elements of The Organizational Climate and The Managing of the Academic Performance, By standing on main hypothesis that(there is significant relationship and effect of the Factors of The Organizational Climate and The Managing of the Academic Performance)depending on the survey by using designed questionnaire distributed on the study sample 50 professors within Five Colleges from AL-Muthana University(the community of the study)within the academic year(2009-2010)in addition to the questionnaire of gathering study data, the searchers also used the personal interviews ,all this data putting with using of SPSS.V.10 ,Program to analyzing it ,The most important finding is that achieving the study hypothesis of finding the relation between the organizational climate factors and the managing of the academi performance.